A Learning Obstacle 11th-Grade Students in Solving Exponential Function Problems and Their Modeling Focus on Critical Thinking Skills - Dwina Saptiani; Tatang Herman; Nanang Priatna (Academic Bright Collaboration, 2026)
Purpose – This study aims to identify the learning obstacles experienced by eleventh-grade students when solving exponential function and modeling problems, particularly those related to critical thinking skills. Methods – A qualitative phenomenological approach was employed involving 30 eleventh-grade students. Data were collected through critical thinking tests, semi-structured interviews, textbook analysis, and focus group discussions. Students’ responses were categorized according to four critical thinking indicators: interpretation, analysis, evaluation, and inference. Findings – The results revealed several learning obstacles across the critical thinking indicators. Students had difficulty interpreting contextual situations, identifying relationships among variables, and understanding decay contexts. Errors in exponent operations and limited understanding of covariational relationships affected analytical reasoning. Students also struggled to predict function behavior without graphical representations and encountered difficulties in drawing conclusions or proposing alternative mathematical models. Research implications – The findings highlight the need for instructional designs that emphasize contextual reasoning, modeling activities, and action–formulation–validation processes to support critical thinking development. Originality – This study integrates critical thinking assessment with learning-obstacle analysis, providing a comprehensive explanation of the difficulties students encounter when solving contextual exponential function problems.